Integrating Electric Buses in Conventional Public Transit: A First Appraisal - Diogo Ribeiro Gomes dos Santos (2016)
Private individual transportation is becoming cumbersome and expensive, as urban traffic turns more chaotic, fuel prices increase and the effects of pollutant emissions become evident. Public transit systems are an answer to reducing the number of cars on the road. Particularly, buses are an attractive alternative, as they mostly depend on pre-existent infrastructure, having no need for complex changes. Making some of these buses electric would mean even less tailpipe emissions and cheaper consumption costs, when compared to fully conventional fleets.However, electric vehicles have disadvantages, such as lower power and autonomy, scarce recharge points on most urban networks and vehicle performance greatly dependent on route characteristics. We can solve this with a more conservative approach - using hybrid fleets, comprised by both electric and conventional buses.This dissertation intends on tackling two main aspects with this kind of fleets: estimating the performance of the integrated electric buses and obtaining optimal balances of both kinds of vehicles. To fulfil these goals, real and simulated data of a bus network in Porto, Portugal, is analysed and heuristic approaches are used to devise hybrid fleet arrangements.This study, supported by real data covering a large scope of the public transit network, in addition to suggesting fleet configurations for the specific network under consideration, also formulates general recommendations towards sustainable urban network planning and management.